Retention properties of six different luting cements on titanium surface - Hakan Akin (Cumhuriyet University, 2014)
Objectives: With conflicting results in the literature and various manufacturer recommendations, implant restorative cements can provide inadequate retention on implants, especially short or single implants. The aim of this study was to evaluate and compare the retentive properties of six different implant restorative cements on titanium surface. Materials and Methods: A total of 120 titanium rods of specimens (10 mm in length and 12 mm in diameter) were divided into 6 experimental groups (n=20) and six different cements were compared: Adhesor (A), Adhesor Carbofine (AC), Cavitan Cem (CC), Meron (M), Implacem (IM), and MIS Crown Set (MIS). Specimens were subjected to shear bond strength test by a universal testing machine with a crosshead speed of 1 mm/min. The data were analyzed with Kruskal-Wallis and Mann-Whitney U tests (α=0.05). Results: The highest mean bond strength was observed in specimens of group MIS, and followed by specimens of group AC. The adhesive failure mode was predominantly observed in all groups. Conclusions: Different cements on titanium surfaces provide different retention levels. Resin cement is the cement of choice for the definitive non-retrievable cementation of crown copings to implant abutments.